Empirical Assessment of Sustainability and Feasibility of Government Debt: The Philippines Case - Duo Qin; Marie Anne Cagas; Geoffrey Ducanes; Nedelyn Magtibay-Ramos; Pilipinas Quising (Asian Development Bank (ADB), 2005)
This paper assesses empirically the sustainability and feasibility of the government debt in the Philippines using the No Ponzi Game criterion. Both historical data and forecasts generated by a quarterly macroeconometric model of the Philippines are used in the assessment. Stochastic simulations are carried out to mimic future uncertainty. The test results show that, up to the end of the present administration in 2010, the Philippine government debt is not sustainable but weakly feasible, that the feasibility is vulnerable to major adverse shocks, and that simple budgetary deficit control policy is inadequate for achieving debt sustainability or strengthening feasibility
hdl:11540/1892
Keywords: 330; Öffentlicher Haushalt; Öffentliche Schulden; Haushaltskonsolidierung; Empirische Methode; Philippinen